Geocartografia: orientações para o trabalho com a Cartografia nos anos iniciais do ensino fundamental - Lima, Maria Venâncio (2021)
Cartography is an integral part of geographical science, it is considered an element of study, understanding and interpretation of spatial phenomena. A critical and analytical reading of the differences that exist in different locations for the perceptive search for the development or not of these spaces. In this sense, this study investigated the cartographic knowledge in Geography classes, present in basic education. We discussed and theoretically questioned facts related to the analysis of the study of space, the reflections of teaching practice in teaching Cartography in the early years of elementary school and teacher training in undergraduate programs, taking into account their practice in the classroom. Subsequently, an empirical research was carried out with geography teachers in the early years of elementary school in municipal schools in Orós, state of Ceará. For this purpose, the Google Form platform was used, with the creation of a link, enabling teachers to answer the proposed questionnaire regarding cartographic knowledge and their performance in the classroom. Thus, the problem of the research carried out was founded, highlighting the difficulties of training and pedagogical performance in cartographic education. It is in the work with the process of construction of cartographic knowledge, starting with cartographic literacy approaches, with a main focus on the search for paths through knowledge, that the student must learn to apply in their daily lives, emphasizing, in this way, the importance of the teacher work so that the student education is enriched, making real this acquired knowledge so that this space is recognized and valued as an educational agent aimed at the well-being of this citizen. In this study, there is the purpose that the school and teachers, through Geography, more specifically Cartography, can evidence this vision of improvement in methodological procedures, based on the observations and responses obtained by the survey carried out with teachers in the municipality of Orós, state of Ceará, and provide teachers with a proposal for help and support with the development of a booklet with didactic sequences, emphasizing cartographic literacy for the early years of elementary school, once the weaknesses or potentials found in the teaching practice of teaching cartographic education, come to contribute and guide the teacher work. Therefore, the work is guided by the search for reflective analyses about cartographic literacy in the early years of elementary school, the training of teachers who work with this audience and a methodological proposal for teaching Cartography as a form of collaboration for teachers.